2017
DOI: 10.1021/acs.analchem.6b04650
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of p-(13C,15N-Cyano)phenylalanine as an Extended Time Scale 2D IR Probe of Proteins

Abstract: Two-dimensional infrared (2D IR) spectroscopy provides a powerful approach for the direct study of molecular dynamics with high spatial and temporal resolution. Its application for investigating specific locations in proteins requires the incorporation of IR probe groups with spectrally isolated absorptions to avoid the congestion inherent to protein spectra. This has motivated extensive efforts toward the development of new IR probes, but there remains a need for those that can extend the experimental time ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…51 In addition, the water solvent itself strongly absorbs the mid-IR pulses, leading to off-diagonal spectral features associated with water heating. 41 For CNPhe, the 2D spectra at T w of 10 ps (Fig. 4A) already show line width distortion due to reduction in signal strength as a result of the fast lifetime of CNPhe.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…51 In addition, the water solvent itself strongly absorbs the mid-IR pulses, leading to off-diagonal spectral features associated with water heating. 41 For CNPhe, the 2D spectra at T w of 10 ps (Fig. 4A) already show line width distortion due to reduction in signal strength as a result of the fast lifetime of CNPhe.…”
Section: Resultsmentioning
confidence: 90%
“…40,41 In H 2 O, the CN lifetime for 13 C 15 NPhe (8.7–10.5 ps) is ~2.0–2.5 fold longer than CNPhe (4.0–4.6 ps), whereas those for 13 CNPhe(3.4–5.0 ps) and C 15 NPhe (0.90–2.2 ps) are roughly the same or even shorter. These are fairly small changes in lifetime and do not correlate with the small changes in mass, which indicates that the increase in mass from isotopic substitution does not substantially decouple the intramolecular vibrational relaxation pathways.…”
Section: Resultsmentioning
confidence: 94%
“…The masses of all CSPNs were in agreement with the theoretical values, which further ensured the purity and synthetic efficacy of SPPS (Figure.S3–S7). Further, the intensity of aromatic C-H stretching was found to be in ascending order from RT to 4F-RT, which can be attributed to the increasing number of Phe,[46] as evident from the FT-IR spectral data (Figure.S8).…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, we develop a simple yet powerful method to extract thermodynamic information about the H-bonding interactions of interest, which is based on the notion that the stretching vibrational frequency (ν CN ) of a cyano (CN) group depends on its H-bonding status. , The sensitivity of the ν CN of various nitriles to its local environment is well documented and studied. For example, Getahun et al have shown that the ν CN of an unnatural amino acid, p -cyanophenylalanine (Phe CN ), is shifted from 2237.2 cm –1 in water to 2228.5 cm –1 in tetrahydrofuran (THF), and other studies, especially those involving peptides and proteins, ,,, have further demonstrated that ν CN depends on the local microenvironment of Phe CN . Although previous studies clearly established that H-bond formation can change the stretching frequency of a CN group, there is no simple correlation that can be used in practice to interpret an observed ν CN in terms of the strength of the underlying H-bonding interactions. Therefore, we aim to develop a method that can yield such information.…”
Section: Introductionmentioning
confidence: 99%